Antimicrobic Activities Of Solid Soap Against Staphylococcus aureus Dan Escherichia coli Human Pathogen Bacteria - Nabilla, A. Nabilla; Advinda, Linda (Jurnal Serambi Biologi, 2022)
Staphylococcus aureus and Escherichia coli are the two types of bacteria that most often attack the human body. Solid bath soap is a soap that is used to clean the body and can function as an antimicrobial if the soap contains antimicrobial ingredients. This study aims to determine the antimicrobial activity of solid bath soap against S. aureus and E. coli bacteria. This research is an experimental study using a completely randomized design (CRD) with 5 treatments, namely A1 (initials: Lx), A2 (initials: Lb), A3 (initials: Gv), A4 (initials: Ct), and A5 (initials: Sz), with 3 repetitions. The method used is the disc diffusion method using a 5 mm diameter paper disc to determine the antimicrobial activity of soap and see the inhibition zone formed in the test medium. The results obtained showed that the antimicrobial activity of solid bath soap had no significant effect on the growth of S. aureus and E. coli bacteria. The highest antimicrobial activity in inhibiting the growth of S. aureus was A2 soap with an inhibition zone diameter of 22,27 mm, and the lowest was A1 soap with an inhibition zone diameter of 12,4 mm. While the highest inhibiting E. coli was A1 soap with an inhibition zone diameter of 20,17 mm, and the lowest was A5 soap with an inhibition zone diameter of 14,37 mm.